Clinical significance of substrate characteristics and ablation outcomes in patients with atrial fibrillation and significant functional mitral regurgitation - Bautista, Jose Antonio L.; Lin, Chin-Yu; Lu, Chi-Ting; Lo, Li-Wei; Lin, Yenn-Jiang; Chang, Shih-Lin; Hu, Yu-Feng; Chung, Fa-Po; Tuan, Ta-Chuan; Chao, Tze-Fan; Liao, Jo-Nan; Chang, Ting-Yung; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) and mitral regurgitation (MR) have a complex interplay. Catheter ablation (CA) of AF may be a potential method to improve the severity of MR in AF patients. Methods Patients with symptomatic AF and moderate to severe MR who underwent catheter ablation from 2011 to 2021 were retrospectively included in the study. Patients' baseline characteristics and electrophysiological features were examined. These patients were classified as group 1 with improved MR and group 2 with refractory MR after CA. Results Fifty patients (age 60.2 ± 11.6 years, 29 males) were included in the study (32 in group 1 and 18 in group 2). Group 1 patients had a lower CHA2DS2-VASc score (1.7 ± 1.5 vs. 2.7 ± 1.5, P = 0.005) and had a lower incidence of hypertension (28.1% vs. 66.7%, P = 0.007) and diabetes mellitus (3.1% vs. 22.2%, P = 0.031) as compared to group 2 patients. Electroanatomic three-dimensional (3D) mapping showed that group 1 patients demonstrated less scars on the posterior bottom of the left atrium compared to group 2 patients (12.5% vs. 66.7%, P < 0.001). AF recurrence was not different between the two groups. After multivariate logistic regression analysis, a posterior bottom scar in the left atrium independently predicted refractory MR despite successful AF ablation. Conclusion Most patients with AF and MR showed improvement of MR after AF ablation. A scar involving the posterior bottom of the left atrium is associated with poor recovery of MR.